Implikasi Hukum Terkait Kemitraan Bisnis Dalam Peningkatan Pemasaran Getas Kering Oleh BUMDES - Niken Ayu Dwi Putri (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Business partnerships in the context of dry brittle marketing by Village-Owned Enterprises (BUMDes) require an in-depth understanding of legal protection for all parties involved. This article discusses the definition of a business partnership, legal implications regarding liability, and legal protections to ensure the sustainability and success of collaboration. Product and service development, rights and obligations in business partnerships, as well as profit and risk management are the focus in dealing with the dynamics of dry brittle marketing. Legal responsibilities, including contract enforcement and dispute resolution, are described as an important foundation. Legal protection for the parties in a business partnership, through signing clear contracts and effective dispute resolution, is necessary to create a successful relationship. This article also discusses dispute resolution mechanisms, such as negotiation, mediation and arbitration, as well as legal implications in increasing the marketing of dry brittle by BUMDes.